Pengambilan Keputusan Petani Terhadap Penggunaan Benih Bawang Merah Lokal dan Impor di Kabupaten Cirebon, Jawa Barat - Theresia, Valentina; Fariyanti, Anna; Tinaprilla, Netti (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
A deficiency of shallot seed production causes Indonesia could not meet its own local demand yet and thus imports foreign variety from other countries. However, farmer should choose between local and imported seed variety for their farming business activity. The purposes of the study was to analyze farmer decision and factors that determine farmer decision to utilize local and imported seed of shallot. Logistic regression was used to answer the research questions. Respondents were 60 persons divided into two groups, farmer who utilized local seed and that utilized the imported one. The result showed that the differences in decision making between local and imported farmers were the benefits they sought, while the factors that significantly influence the farmers decision to use local seed are scale of land area, seed price, income and market. Scale of land area and seed price have negative influence significantly, while income and market give positive influence significantly on farmer decision to utilize conventional seed.